The Abilities of Junior High School Students in Solving PISA-Like Mathematical Problems on Uncertainty and Data Contents - Sujadi, Imam; Budiyono; Kurniawati, Ira; Wulandari, Arum Nur; Andriatna, Riki; Puteri, Hanifa Alifia (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Indonesia's participation in PISA is less satisfactory, particularly in mathematics. Uncertainty and data are two of the PISA content areas being evaluated. Therefore the aim of this study is to analyze students' abilities to solve mathematical problems such as PISA on uncertainty and data content to map student readiness for PISA. This study is kind of qualitative study used a case study design. The sample in this study was 84 students of grade IX junior high school who were selected with a simple random sampling technique. The data collection method employs both test and non-test instruments. The data analysis technique used in this study consist of data reduction, data presentation, and conclusion and verification. The results showed that 689 students scored out of 1344, representing 51.41%. These results show that students' ability to solve math problems such as PISA on uncertainty and data content is in the moderate category. While each material, namely statistics and opportunities, is in the high and low categories. This condition is based on learning that has yet to lead students to contextual problems. With these results, it is hoped that there will be efforts to improve the learning process by involving problems such as PISA as habituation.